ANALISIS LEVEL KECERDASAN EMOSIONAL BELAJAR MATEMATIKA SISWA BERDASARKAN GENDER PADA MASA COVID - Teti Teti; Marzuki Ahmad; Sinar Depi Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The study aims to analyze students’ mathematic learning emotional intelligence level based on gender in covid period. The approach of the research uses descriptive quantitative with 10 students as the respondents. Instrument of the research uses questionnaire (Linkert Scale) and interview. The result of the research shows male and female students who have high emotional intelligence able to understand the condition of self and others, able to control feeling, and able to interact to the friends and teachers. Male students who have medium emotional intelligence able to control his emotion but they are not able for the others, able interact to their friends but they are not able to the teachers. Female students who have medium emotional intelligence able to to control herself and the others, they able to interact to the teacher but they are not able to their friends. Male students who have low emotional intelligence able to control his self but they are not able to interact to the teachers and friends to get the help. Female students who have low emotional intelligence are not able to control herself and the others and they are not able to interact to the teachers and friends to get help.